Feasibility of Predicting Soft Biometric Traits Based on Keystroke Dynamics Characteristics - Roy, Soumen; Roy, Utpal; Sinha, DD (International Journal of Computer Sciences and Engineering, 2025)
This study investigates the feasibility of identifying age group, gender, handedness and number of hand(s) used of a user by measuring the typing pattern on a computer keyboard which has good impact on keystroke dynamics biometric user authentication system. Fuzzy-Rough Nearest Neighbour (FRNN) with the help of Vaguely Quantified Rough Set (VQRS) machine learning method was used to develop the model based on the collected typing pattern and evaluated the effectiveness of the classifier in this domain. Multiple benchmark datasets have been used to validate the proposed model in order to check the robustness of the proposed approach. The obtained results indicate that age group, gender, handedness, and a number of hand(s) used can be predicted by the way user type on a computer keyboard for a single predefined text. It is also observed that incorporation of such soft biometric traits as extra features with primary keystroke dynamics characteristics can be used to enhance the performance of keystroke dynamics systems pretending to be used in future at low cost. The model is developed with a limited number of samples collected from a small group of participants in a controlled environment. However, this model will be further trained and evaluated by some extra features which are easily available in each smartphone such as gyroscope and acceleration information. Identifying such traits are important issues in digital forensics, age-based access control, targeted advertisement and auto profiling of the users. It adopts a suitable method to be used on the desktop computer as well as a smartphone.